2023
DOI: 10.2174/0929866530666230525162545
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Function of Cholesterol Oxidase: A Review

Abstract: Cholesterol was first found in gallstones as an animal sterol; hence it is called cholesterol. Cholesterol oxidase is the chief enzyme in the process of cholesterol degradation. Its role is obtained by the coenzyme FAD, which catalyzes the isomerization and oxidation of cholesterol to produce cholesteric 4-ene-3-ketone and hydrogen peroxide at the same time. Recently, a great advance has been made in the discovery of the structure and function of cholesterol oxidase, and it has proven added value in clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 136 publications
0
0
0
Order By: Relevance
“…Pseudomonas sp. P17 strain as a potential PGPR for plant growth and nutrient uptake in sorghum, as inoculation lead to better growth, higher nutrient uptake and seedlings treated, as well as appropriate root volume, maximum dry mass, shoot length, chlorophyll, leaf area, phosphorus, nitrogen, carbohydrates and other nutrients [309][310][311][312]. Saad and Abo-Koura [313] reported that inoculation of sorghum plants with Bacillus cereus could improved vegetative growth, RWC% but reduced antioxidant enzymes under drought stress.…”
Section: Plant Growth-promoting Bacteria and Sorghummentioning
confidence: 99%
“…Pseudomonas sp. P17 strain as a potential PGPR for plant growth and nutrient uptake in sorghum, as inoculation lead to better growth, higher nutrient uptake and seedlings treated, as well as appropriate root volume, maximum dry mass, shoot length, chlorophyll, leaf area, phosphorus, nitrogen, carbohydrates and other nutrients [309][310][311][312]. Saad and Abo-Koura [313] reported that inoculation of sorghum plants with Bacillus cereus could improved vegetative growth, RWC% but reduced antioxidant enzymes under drought stress.…”
Section: Plant Growth-promoting Bacteria and Sorghummentioning
confidence: 99%